Heritage Language and Culture Maintenance: A Study of Armenian Ethnic Cultural Center - Kozhabayeva, Kamila (Nazarbayev University Graduate School of Education, 2017)
Situated in Central Asia, Kazakhstan is an ethnically diverse post-Soviet country, where more than 463 ethnic community schools, called ethnic cultural centers, operate under supervision and protection of government. Armenians are one of the smaller ethnic minority groups in Kazakhstan, accounting for only 33000 persons, who managed to successfully maintain ethnic culture and language (Karapetyan, 2015). As majority of existing literature on heritage language and culture maintenance focuses on immigrants in mono-/multilingual countries where the majority language is widely spoken, this qualitative case study reveals the situation of forced migrants who live in multilingual context with the majority language, Kazakh, being revitalized. The study answered the research questions about socio-cultural practices of the Armenian ethnic center, challenges that the center administration and attendees face, and how the center participants perceive the center and why they continue attending it. Qualitative face-to-face interviews and non-participant observation of the event hosted by the center show that practising language and culture during the bonding gatherings within the ethnic community plays essential role in maintaining heritage language and culture in multilingual context. Although the center currently experiences lack of participant engagement, especially youth participants, absence of teachers of Armenian, problems with office and center facilities and lack of center resources, participants and administration reported the positive effect of the center’s work. Thus, attending the center helped participants gain the sense of ethnic community, maintain and, for some of them, learn Armenian language and culture, and gain the sense of acceptance and appreciation in Kazakhstan. These findings emphasize the importance of Kazakhstani ethnic cultural centers in developing and supporting ethnic diversity and highlight the ways in which government and center administration can improve the work of the centers. Казахстан – это многонациональное, постсоветское государство, расположенное в Средней Азии, где функционирует более 463 домов культуры различных этнических групп. Они именуются этнокультурными центрами, и находятся под поддержкой и защитой правительства. Армяне - одна из самых малочисленных этнических групп Казахстана, которая составляет около 33000 человек. Тем не менее им успешно удалось сохранить культуру и язык культурного наследия (Карапетян, 2015). Большинство существующей литературы по сохранению культуры и языка культурного наследия ориентируется на изучение иммигрантов в моно-/полиязычных странах, где свободно говорят на официальном языке. Однако, данное квалитативное исследование по методу кейс стади освещает ситуацию вынужденных переселенцев, которые сейчас живут в многоязычном контексте, где языком большинства, казахский, находится в процессе восстановления. Исследование ответило на поставленные вопросы о социокультурных методах, применяемых в армянском этническом центре, выявило трудности, с которыми сталкиваются администрация и члены центра, показало, что члены центра думают о центре и почему они продолжают посещать его. Индивидуальные интервью и наблюдение мероприятия, организованного центром, показали, что практика языком и культуры во время сближающих мероприятий в этническом сообществе играет существенную роль в сохранении культуры и языка культурного наследия в многоязычном контексте. Армянский центр в настоящее время испытывает трудности, связанные с недостаточным уровнем активности участников центра, особенно молодежи, отсутствием учителей армянского языка, проблемами с офисом и удобствами, и недостатком ресурсов центра. Несмотря на это, члены центра и администрации сообщили о положительном эффекте работы центра. Таким образом, посещение и участие в мероприятиях центра помогло участникам исследования приобрести чувство этнического сообщества, сохранить, а для некоторых из них – выучить, армянский язык и культуру, и приобрести чувство принятия и уважения в Казахстане. Эти результаты подчеркивают важность казахстанских этнокультурных центров в развитии и поддержке этнического разнообразия и указывают на то, как правительство и администрация центра могут улучшить работу центров.
Keywords: heritage language; culture maintenance; ethnic minorities; multilingual countries; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education